Developing resilient financial wellbeing among elderly citizens in Malaysia - Noraina Mazuin, Sapuan; Mohd Nur Fadzly, Basar (Springer, Cham, 2022)
The globe is aging, and the number of old people is increasing. Presently, Malaysia is one of the world's aging countries. With long life expectancy, less income, and limited financial knowledge, elderly people in Malaysia are seen as helpless in their old age and drastic measures need to be taken, especially by the government to improve the financial wellbeing and quality of life of this group. Even though a great deal of research has been done on the saving behaviour of the aging population, yet, no research has attempted to model and validate the financial wellbeing of elderly retired people in Malaysia. Thus, this study is done looking at previous literature on how to develop financial and digital literacy among Malaysian elderly to ensure they have adequate financial resources and the ability to adapt to new technology in managing their financial assets. The finding of this study indicated that the “Cognitive-Readiness-Opportunity-Internal Values-Technology Adoption Model”, can become an important model concerning the development of an elderly peoples’ financial wellbeing in retirement. The outcome of this study will complement the Malaysian National Strategic Thrust (Improving wellbeing for all) and SDG Agenda 2030 to achieve zero poverty, especially among elderly people.